2004
DOI: 10.4319/lo.2004.49.2.0415
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of the δC and δN of particulate and dissolved carbon and nitrogen in Lake Lugano: Constraints on biogeochemical cycling in a eutrophic lake

Abstract: We determined the ␦ 13 C and ␦ 15 N of water-column particulate organic matter (POM), dissolved inorganic carbon, and nitrate, together with water chemistry and phytoplankton biomass and species composition every month in eutrophic Lake Lugano. As primary productivity increased during spring, the ␦ 13 C of photic-zone POM increased from Ϫ34‰ to Ϫ24‰. This 13 C enrichment reflects decreasing C-isotope fractionation between organic and inorganic carbon pools in response to decreasing surface water [CO 2 (aq)]. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
190
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(216 citation statements)
references
References 64 publications
(106 reference statements)
17
190
6
Order By: Relevance
“…Our findings, however, are significantly different from the results of other studies on the dynamics of the stable carbon isotope composition of POM in lacustrine ecosystems: Lehmann et al (2004a), for example, have demonstrated that in Lake Lugano the total annual POM flux did not directly reflect variations in phytoplankton primary production. Also the annual flux-weighted d 13 C POM values did not correlate with the amount of annual phytoplankton primary production, as is the case in Lake Holzmaar.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings, however, are significantly different from the results of other studies on the dynamics of the stable carbon isotope composition of POM in lacustrine ecosystems: Lehmann et al (2004a), for example, have demonstrated that in Lake Lugano the total annual POM flux did not directly reflect variations in phytoplankton primary production. Also the annual flux-weighted d 13 C POM values did not correlate with the amount of annual phytoplankton primary production, as is the case in Lake Holzmaar.…”
Section: Discussioncontrasting
confidence: 99%
“…Alternatively, these results suggest that the processes leading to depleted d 13 C DIC signatures in the hypolimnion were predominantly microbial degradation of DOC (producing d 13 C CO2 from À28.0‰ to À26.3‰, Table 5) and/or CH 4 oxidation (producing d 13 C CO2 from À63.0‰ to À47.5‰) [Jedrysek, 1995]. The relationships between [DIC] À1 and d 13 C DIC shown in Figure 5c for the wood harvested lakes (spring: r 2 = 0.34, p < 0.05) and in Figure 5d for the wood harvested reservoir (spring and summer: r 2 = 0.81, p < 0.0001 and r 2 = 0.50, p < 0.0001, respectively) suggest that the concentration and stable isotope composition of the DIC pool were mostly controlled by the combined influence of DOC degradation (causing low [DIC] À1 and d 13 C DIC depletion), photosynthesis and photo-oxidation (causing high [DIC] À1 and d 13 C DIC enrichment) in these systems [Lehmann et al, 2004;McCallister and del Giorgio, 2008;Vähätalo and Wetzel, 2008].…”
Section: Sources Of Ommentioning
confidence: 91%
“…[35] To identify the relationship between FPOM sources and their relationship to DIC Lehmann et al, 2004], d 13 C DIC was plotted against the d 13 C POC of the FPOM fraction (d 13 C POC , Figure 6). The spring d 13 C POC results presented in Figures 6a and 6b show that water bodies with a non-harvested watershed were dominated by algal OM.…”
Section: Sources Of Ommentioning
confidence: 99%
“…The stable nitrogen isotope ratio (d 15 N) of particulate organic matter (POM) has been used as an indicator for the source, availability and the cycling processes of nitrogen in lakes (Gu et al, 1996;Teranes and Bernasconi, 2000;Lehmann et al, 2004;Gu et al, 2006). Previous studies have revealed that d 15 N POM varies over time in individual lakes (Gu et al, 1994(Gu et al, , 2006Lehmann et al, 2004;Syva¨ranta et al, 2008;Hadas et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that d 15 N POM varies over time in individual lakes (Gu et al, 1994(Gu et al, , 2006Lehmann et al, 2004;Syva¨ranta et al, 2008;Hadas et al, 2009). Several studies have compared d 15 N POM among lakes.…”
Section: Introductionmentioning
confidence: 99%